Inventorizing Selected Archaeological and Cultural Heritage Sites of Ghana - Asare, K. (University of Ghana, 2021)
Ghana has many archaeological and cultural heritage sites. However, the country lacks a comprehensive inventory of these assets. This makes it impracticable to effectively manage Ghana’s archaeological and cultural heritage resources, and put the resources at risk of destruction. Archaeological, historic, and cultural heritage sites are, for example destroyed indiscriminately by large-scale earth-moving construction and other infrastructural development activities. This pilot digital heritage inventory project uses computer software programmes, such as ArcGIS, Microsoft Excel and Word to document, annotate, profile, graphically represent and develop an inventory of nine selected archaeological and cultural heritage sites in Ghana. The study also uses desk research (literature search and review), collection of oral narratives, site visits, photography to gather complementary research data. This work is expected to create awareness, enhance the conservation, safeguarding and overall management of the selected sites and other heritage sites in the country. It is recommended that this inventory compilation be continued and more sites should be added to this inventory.
MPhil. Archaeology
Keywords: Ghana; Archaeological